Musical Organics: A Heterarchical Approach to Digital Organology. Issue 3 (3rd July 2017) - Magnusson, Thor
Abstract: Gaining a comprehensive understanding and overview of new musical technologies is fraught with difficulties. They are made of digital materials of such diverse origins and nature, that they do not fit comfortably into traditional organological classifications. This article traces the history of musical instrument classifications relevant to the understanding of new digital instruments, and proposes an alternative method to the centuries-old tree-structure of downwards divisions. The proposed musical organics is a multidimensional, heterarchical, and organic approach to the analysis and classification of both traditional and new musical instruments that suits the rhizomatic nature of their material design and technical origins. Outlines of a hypothetical organological informatics retrieval system are also presented.